2021
DOI: 10.3390/ijerph18094715
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Sustainable Mobility: A Perspective from Car and Public Transport Users

Abstract: Sustainable mobility is becoming a key factor in improving the quality of life of the residents and increasing physical activity (PA) levels. The current situation of sustainable mobility and its analysis is a first step in understanding the factors that would encourage residents to discover and choose alternative modes of travel. The present study examined the factors that encourage the choice of active modes of travel among urban adult population. Walking and cycling were analyzed as the most sustainable for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Farmers, mechanics, power plant operators, workers on production lines, on the road, and electricians are a few examples of blue-collar occupations [17], [18], [19]. On the other hand, whitecollar professions often involve office work in clerical, administrative, Teachers, professors, researchers, human resources agents, accounting and processing staff, office managers, business executives, public relations and advertising specialists, architects, engineers, stockbrokers, medical experts (including dentists, doctors, and nutritionists), and managerial jobs, among others [20]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Farmers, mechanics, power plant operators, workers on production lines, on the road, and electricians are a few examples of blue-collar occupations [17], [18], [19]. On the other hand, whitecollar professions often involve office work in clerical, administrative, Teachers, professors, researchers, human resources agents, accounting and processing staff, office managers, business executives, public relations and advertising specialists, architects, engineers, stockbrokers, medical experts (including dentists, doctors, and nutritionists), and managerial jobs, among others [20]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A study in Lithuania showed that only 13.5% used active modes of traveling (cycling and walking), and those who used other modes of transport perceived those active modes as the most sustainable. Safer pedestrian crossings and comfortable paths encourage walking, while broader and safer cycling networks promote cycling [35].…”
Section: Transport Infrastructure Evaluationmentioning
confidence: 99%
“…Proliferation of sustainable mobility requires a change in people's mindset and the promotion of sustainable travel habits (Bruun & Givoni, 2015;Suchanek & Szmelter-Jarosz, 2019). Education and campaigns that promote awareness of the environmental and social impacts of transport, play a crucial role, since they contribute to changes in people's travel habits and behavior (Dėdelė & Miškinytė, 2021;Guglielmetti Mugion et al, 2018;OECD, 2002). Children are a key target group, as their mobility choices and habits will shape future mobility (Kelly & Fu, 2014;Mammen et al, 2014a;2014b;Napier et al, 2011).…”
Section: Introductionmentioning
confidence: 99%